Preparation process of hot melt adhesive with high viscosity and high shear strength

By treating iron trioxide and nano calcium carbonate, and combining with EVA resin and other materials, a hot melt adhesive with high viscosity and high shear strength is prepared, which solves the problem of insufficient adhesiveness of existing hot melt adhesives. , improves the mechanical properties and dispersion of the material.

CN119264837AInactive Publication Date: 2025-01-07LINYI QINZHENG COMPOSITE MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411490797.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing hot melt adhesives are not viscous during use and have low shear strength, making it difficult to meet the high viscosity requirements of certain applications.

Method used

By pretreating iron tetraoxide and modifying nano calcium carbonate, composite particles and modified nano calcium carbonate are formed, which improves its dispersion and compatibility in the matrix, combined with EVA resin, antioxidants, and rosin. A twin-screw extrusion process with paraffin was carried out to prepare hot melt adhesives with high viscosity and high shear strength.

Benefits of technology

It significantly improves the mechanical properties, shear strength and viscosity of hot melt adhesives, forms a stable dispersion system, and enhances the overall mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264837A_ABST
    Figure CN119264837A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of a hot melt adhesive with high viscosity and high shear strength, and relates to the technical field of hot melt adhesives, the preparation process comprises the following preparation steps: step 1, adding 30-35mL of deionized water into 5-8 parts of modified nano calcium carbonate, and carrying out ultrasonic dispersion; step 2, pouring 55-70 parts of EVA resin into a reaction kettle, adding the mixed solution in the step 1 and 5-12 parts of ferroferric oxide composite particles, heating to 45-50 DEG C, and uniformly mixing; and step 3, adding 0.3-0.7 part of an antioxidant 1010, 8-12 parts of rosin and 16-20 parts of paraffin, continuously heating to 65-70 DEG C, and uniformly mixing. According to the preparation process of the high-viscosity and high-shear-strength hot melt adhesive, ferroferric oxide is treated, so that the surface of the ferroferric oxide is coated with a layer of organic matter, the dispersity of the ferroferric oxide in a matrix is improved, hydroxyl on the surface of the ferroferric oxide reacts with vinyl acetate, and the viscosity of the ferroferric oxide is improved. The compatibility and the tuberculosis between ferroferric oxide and a matrix can be remarkably improved, so that the mechanical property, the shear strength and the viscosity of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hot melt adhesives, in particular to a preparation process of a hot melt adhesive with high viscosity and high shear strength. Background Art

[0002] Hot melt adhesive is a kind of thermoplastic adhesive that can be applied in a hot melt state and bonded after cooling into a solid state. It is mainly composed of thermoplastic polymers. Hot melt adhesive has the advantages of rapid curing, no solvent, strong shape plasticity, repeated melting and bonding, and bonding of various materials. It has the advantages of less pollution, environmental protection and safety, and easy transportation and storage. It is widely used in construction materials, electronic appliances, new energy, packaging and other fields.

[0003] The Chinese patent with publication number CN106010368A discloses a method for preparing a cold-resistant hot melt adhesive, which relates to the field of hot melt adhesive technology. The method comprises the following steps: putting polyethylene wax into a mixer and heating it to melt, adding the remaining materials into the mixer, heating it to 140°C, and stirring it for 1 to 2 hours at 200 to 300 rpm; extruding the evenly stirred mixture into granules with an extruder, setting the barrel heating temperature to 158 to 185°C, and the screw speed to 350 to 500 rpm. After the material is extruded, it is cooled and cut in a water tank to obtain the obtained product. This invention solves the problem that the existing hot melt adhesive has poor cold resistance, is prone to brittle cracking at low temperatures, and has reduced viscosity. However, the viscosity of the hot melt adhesive prepared by the above-mentioned prior art needs to be further improved during use. To this end, the present invention provides a preparation process for a hot melt adhesive with high viscosity and high shear strength to solve the above problems. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a process for preparing a hot melt adhesive with high viscosity and high shear strength, which solves the problems mentioned in the above background technology.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A preparation process of a hot melt adhesive with high viscosity and high shear strength, comprising the following preparation steps: Step 1: Add 30-35 mL of deionized water to 5-8 parts of modified nano calcium carbonate and disperse by ultrasonication; Step 2: Pour 55-70 parts of EVA resin into a reaction kettle, add the mixed solution in step 1 and 5-12 parts of ferrosoferric oxide composite particles, heat to 45-50° C. and mix well; Step 3: Add 0.3-0.7 parts of antioxidant 1010, 8-12 parts of rosin, and 16-20 parts of paraffin, continue heating to 65-70°C, and mix well; Step 4: adding the uniformly mixed material into a twin-screw extruder for extrusion, and then cooling and granulating to obtain a hot melt adhesive with high viscosity and high shear strength; The twin-screw extruder is divided into three sections: an inlet section, a middle section and an outlet section, and the temperatures thereof are controlled at 75-90°C, 110-125°C and 90-100°C respectively.

[0006] Preferably, the preparation method of the ferrosoferric oxide composite particles is: S1, pre-treating 10-12g of ferrosoferric oxide; S2, pour the treated ferroferric oxide into 25-30 mL of polyvinyl alcohol aqueous solution, ultrasonically disperse for 25-30 min, and introduce nitrogen for protection; S3, add 5-8g of vinyl acetate dropwise, react for 30-40min, raise the temperature to 75-80°C, add 0.8-1.5mL of initiator, react for 30-35min, then add 5-8g of vinyl acetate dropwise, repeat this operation until all the vinyl acetate is added dropwise; S4, adding 10-12 mL of divinylbenzene to adjust the pH value of the solution to 6.8-7.2; S5. Heat to 80-85°C and keep warm for 55-60 minutes; S6. After natural cooling, place in a magnet. After adsorption is completed, pour out the supernatant and rinse the adsorbate with deionized water 3-5 times; S7. Dry in a vacuum drying oven at 70-75°C for 8-10 hours to obtain ferrosoferric oxide composite particles.

[0007] Preferably, in S3, the added amount of vinyl acetate is 40-50g.

[0008] Preferably, the mass fraction of the polyvinyl alcohol aqueous solution is 4%; and the initiator is ammonium persulfate.

[0009] Preferably, in S1, the specific method of pretreatment is: pour 320-350 mL of deionized water into 10-12 g of ferroferric oxide, and perform ultrasonic dispersion, heat to 80-85°C, drop 8-11 mL of oleic acid, stir, and keep warm for 50-60 minutes, rinse with deionized water and anhydrous ethanol for 4-6 times, and then place in a vacuum drying oven to dry for 22-24 hours.

[0010] Preferably, the pretreatment process of ferroferric oxide is carried out under a nitrogen atmosphere; when oily acid is added dropwise, the drop rate is 4-6 drops / min; and the stirring rate during the reaction is 300-350 r / min.

[0011] Preferably, the preparation method of the modified nano calcium carbonate is: Ⅰ. Pour hexadecyltrimethylammonium bromide into deionized water at room temperature and stir until completely dissolved to obtain solution 1; Ⅱ. Add nano calcium carbonate to anhydrous ethanol under stirring, stir for 10-15 minutes, and then ultrasonically disperse for 15-20 minutes to obtain solution 2; III. Mix solution 1 and solution 2, and then add ammonia water to adjust the pH value of the solution to 9.6-10; IV. Centrifugal separation, and drying the precipitate in a vacuum drying oven at 85-90°C to obtain modified nano calcium carbonate.

[0012] Preferably, the weight proportions of the components added in the modified nano-calcium carbonate are: 3-7 parts of hexadecyltrimethylammonium bromide, 20-26 parts of deionized water, 35-50 parts of anhydrous ethanol, and 22-28 parts of nano-calcium carbonate.

[0013] The present invention provides a preparation process of a hot melt adhesive with high viscosity and high shear strength. Compared with the prior art, it has the following beneficial effects: (1) The preparation process of the hot melt adhesive with high viscosity and high shear strength is to treat ferroferric oxide so that its surface is coated with a layer of organic matter, thereby improving the dispersibility of ferroferric oxide in the matrix, and the hydroxyl groups on the surface of ferroferric oxide react with vinyl acetate to significantly improve the compatibility and nodularity between ferroferric oxide and the matrix, thereby improving the mechanical properties, shear strength and viscosity of the material.

[0014] (2) The preparation process of the hot melt adhesive with high viscosity and high shear strength is to modify the nano-calcium carbonate so that it can form a good interface with the matrix, thereby effectively transferring stress and improving the overall mechanical properties of the material; at the same time, the dispersion performance of the nano-calcium carbonate in the matrix is ​​improved to form a stable dispersion system and improve the viscosity of the hot melt adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The SEM images of the nano calcium carbonate before and after modification provided by the present invention; Figure 2 The SEM image of the ferroferric oxide and the ferroferric oxide composite particles provided by the present invention; Figure 3 A comparison chart of the peel strength test provided by the present invention; Figure 4 A comparison chart of mechanical properties tests provided by the present invention; Figure 5 This is a comparison chart of the shear strength test provided by the present invention. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Example 1 A preparation process of a hot melt adhesive with high viscosity and high shear strength comprises the following preparation steps: Step 1: Add 30 mL of deionized water to 5 g of modified nano calcium carbonate and disperse by ultrasonication; The preparation method of the modified nano calcium carbonate is as follows: under room temperature, pour 3 g of hexadecyltrimethylammonium bromide into 20 g of deionized water, stir until completely dissolved, and obtain solution one; under stirring, add 22 g of nano calcium carbonate to 35 g of anhydrous ethanol, stir for 10 minutes, and ultrasonically disperse for 15 minutes to obtain solution two; after mixing solution one and solution two, add ammonia water to adjust the pH value of the solution to 9.6; centrifuge and separate, and place the precipitate in a vacuum drying oven at 85°C to dry, so as to obtain the modified nano calcium carbonate; Step 2: Pour 70g of EVA resin into a reaction kettle, add the mixed solution in step 1 and 12g of ferrosoferric oxide composite particles, heat to 45°C and mix well; Wherein, the preparation method of ferroferric oxide composite particles is: S1. Pre-treat ferroferric oxide: under nitrogen atmosphere, pour 320 mL of deionized water into 10 g of ferroferric oxide, and perform ultrasonic dispersion. After heating to 80°C, add 8 mL of oleic acid at a drop rate of 4 drops / min, stir at a stirring rate of 300 r / min for 55 min, keep warm for 50 min, rinse with deionized water and anhydrous ethanol 4 times in sequence, and then dry in a vacuum drying oven for 22 h. S2, pour the treated ferroferric oxide into 25 mL of a 4% polyvinyl alcohol aqueous solution, ultrasonically disperse for 25 minutes, and introduce nitrogen for protection; S3, add 5 g of vinyl acetate, react for 30 min, heat to 75 ° C, add 0.8 mL of ammonium persulfate, react for 30 min, then add 5 g of vinyl acetate, repeat this operation until all the vinyl acetate is added; S4, add 10 mL of divinylbenzene, adjust the pH value of the solution to 6.8, then heat to 80°C and keep warm for 55 min; S5. After natural cooling, place the mixture in a magnet. After adsorption is completed, pour out the supernatant and rinse the adsorbate with deionized water for 3 times. S6, drying in a vacuum drying oven at 70°C for 8 hours to obtain ferrosoferric oxide composite particles; Step 3: Add 0.7g of antioxidant 1010, 12g of rosin, and 20g of paraffin, continue heating to 65°C, and mix well; Step 4: adding the uniformly mixed material into a twin-screw extruder for extrusion, and then cooling and granulating to obtain a hot melt adhesive with high viscosity and high shear strength; The twin-screw extruder is divided into three sections: an inlet section, a middle section and an outlet section, and the temperatures thereof are controlled at 75°C, 110°C and 90°C respectively.

[0018] Example 2 A preparation process of a hot melt adhesive with high viscosity and high shear strength comprises the following preparation steps: Step 1: Add 32 mL of deionized water to 6 g of modified nano calcium carbonate and disperse by ultrasonication; The preparation method of the modified nano calcium carbonate is as follows: under room temperature, pour 5 g of hexadecyltrimethylammonium bromide into 23 g of deionized water, and stir until completely dissolved to obtain solution one; under stirring, add 25 g of nano calcium carbonate to 40 g of anhydrous ethanol, stir for 12 minutes, and ultrasonically disperse for 18 minutes to obtain solution two; after mixing solution one and solution two, add ammonia water to adjust the pH value of the solution to 9.8; centrifuge and separate, and place the precipitate in a vacuum drying oven at 88°C to dry, so as to obtain the modified nano calcium carbonate; Step 2: Pour 58g of EVA resin into a reaction kettle, add the mixed solution in step 1 and 10g of ferrosoferric oxide composite particles, heat to 48°C and mix well; Wherein, the preparation method of ferroferric oxide composite particles is: S1. Pre-treat ferroferric oxide: under nitrogen atmosphere, pour 330 mL of deionized water into 11 g of ferroferric oxide, and perform ultrasonic dispersion. After heating to 82°C, add 10 mL of oleic acid at a drop rate of 5 drops / min, stir at a stirring rate of 330 r / min for 57 min, keep warm for 55 min, rinse with deionized water and anhydrous ethanol 5 times in sequence, and then dry in a vacuum drying oven for 23 h. S2, pour the treated ferroferric oxide into 27 mL of a 4% polyvinyl alcohol aqueous solution, ultrasonically disperse for 28 minutes, and introduce nitrogen for protection; S3, add 7g of vinyl acetate dropwise, react for 35min, raise the temperature to 78°C, add 1.2mL of ammonium persulfate, react for 32min, then add 7g of vinyl acetate dropwise, repeat this operation until all the vinyl acetate is added dropwise; S4, add 11 mL of divinylbenzene, adjust the pH value of the solution to 7.0, then heat to 83 ° C and keep warm for 57 min; S5. After natural cooling, place the mixture in a magnet. After adsorption is completed, pour out the supernatant and rinse the adsorbate with deionized water for 4 times. S6, placing in a vacuum drying oven at 73°C and drying for 9 hours to obtain ferrosoferric oxide composite particles; Step 3: Add 0.5g of antioxidant 1010, 10g of rosin, and 18g of paraffin, continue heating to 68°C, and mix well; Step 4: adding the uniformly mixed material into a twin-screw extruder for extrusion, and then cooling and granulating to obtain a hot melt adhesive with high viscosity and high shear strength; The twin-screw extruder is divided into three sections: an inlet section, a middle section and an outlet section, and the temperatures thereof are controlled at 85°C, 115°C and 95°C respectively.

[0019] Example 3 A preparation process of a hot melt adhesive with high viscosity and high shear strength comprises the following preparation steps: Step 1: Add 35 mL of deionized water to 8 g of modified nano calcium carbonate and disperse by ultrasonication; The preparation method of the modified nano calcium carbonate is as follows: under room temperature, pour 7 g of hexadecyltrimethylammonium bromide into 26 g of deionized water, stir until completely dissolved, and obtain solution one; under stirring, add 28 g of nano calcium carbonate to 50 g of anhydrous ethanol, stir for 15 minutes, and ultrasonically disperse for 20 minutes to obtain solution two; after mixing solution one and solution two, add ammonia water dropwise to adjust the pH value of the solution to 10; centrifuge and separate, and place the precipitate in a vacuum drying oven at 90°C to dry, so as to obtain the modified nano calcium carbonate; Step 2: Pour 55g of EVA resin into a reaction kettle, add the mixed solution in step 1 and 5g of ferrosoferric oxide composite particles, heat to 50°C and mix well; Wherein, the preparation method of ferroferric oxide composite particles is: S1. Pre-treat ferroferric oxide: under nitrogen atmosphere, pour 350 mL of deionized water into 12 g of ferroferric oxide, and perform ultrasonic dispersion. After heating to 85°C, add 11 mL of oleic acid at a drop rate of 6 drops / min, stir at a stirring rate of 350 r / min for 60 min, keep warm for 60 min, rinse with deionized water and anhydrous ethanol 6 times in sequence, and then dry in a vacuum drying oven for 24 h. S2, pour the treated ferroferric oxide into 30 mL of a 4% polyvinyl alcohol aqueous solution, ultrasonically disperse for 30 minutes, and introduce nitrogen for protection; S3, add 8 g of vinyl acetate, react for 40 min, raise the temperature to 80 ° C, add 1.5 mL of ammonium persulfate, react for 35 min, then add 8 g of vinyl acetate, repeat this operation until all the vinyl acetate is added; S4, add 12 mL of divinylbenzene, adjust the pH value of the solution to 7.2, then heat to 85°C and keep warm for 60 min; S5. After natural cooling, place the mixture in a magnet. After adsorption is completed, pour out the supernatant and rinse the adsorbate with deionized water for 5 times. S6, placing in a vacuum drying oven at 75°C and drying for 10 hours to obtain ferrosoferric oxide composite particles; Step 3: Add 0.3g of antioxidant 1010, 8g of rosin, and 16g of paraffin, continue heating to 70°C, and mix well; Step 4: adding the uniformly mixed material into a twin-screw extruder for extrusion, and then cooling and granulating to obtain a hot melt adhesive with high viscosity and high shear strength; The twin-screw extruder is divided into three sections: an inlet section, a middle section and an outlet section, and the temperatures thereof are controlled at 90°C, 125°C and 100°C respectively.

[0020] Comparative Example 1 Compared with Example 1, the modified nano-calcium carbonate in Example 1 is replaced by nano-calcium carbonate.

[0021] Comparative Example 2 Compared with Example 1, the ferrosoferric oxide composite particles in Example 1 are replaced by ferrosoferric oxide.

[0022] 180° peel strength: Tested using a universal tensile testing machine in accordance with GB / T 2790-1995; the results are as follows Figure 3 shown.

[0023] Tensile properties: Tested using a universal tensile testing machine in accordance with CB / T 528-1998; the results are as follows Figure 4 shown.

[0024] Shear strength test: Tested in accordance with GB / T 7124-2008; the results are as follows Figure 5 shown.

[0025] like Figure 1As shown in the figure, the nano-calcium carbonate before modification is aggregated, while the aggregates of the nano-calcium carbonate after modification are significantly reduced and more evenly dispersed. This is because the surface of the nano-calcium carbonate particles is electronegative under alkaline conditions, which allows CTAB to interact with the nano-calcium carbonate particles through electrostatic forces, forming a hexadecyltrimethylammonium bromide adsorption layer on the surface of the particles. The electrostatic repulsion between the particles effectively prevents the aggregation of the nano-calcium carbonate particles, and thus has a better dispersion effect than the unmodified particles.

[0026] like Figure 2 As shown, the particle size of the ferroferric oxide composite particles is significantly larger than that of the pure ferroferric oxide particles. Before being coated, the particles have high surface energy and magnetic properties, so the particle agglomeration phenomenon is more serious. After coating, the agglomeration phenomenon is significantly improved, and the surface of the ferroferric oxide is coated with a layer of organic matter.

[0027] At the same time, the contents not described in detail in this specification belong to the existing It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0028] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a hot melt adhesive with high viscosity and high shear strength, characterized in that: The method comprises the following preparation steps: Step 1: Add 30-35 mL of deionized water to 5-8 parts of modified nano calcium carbonate and disperse by ultrasonication; Step 2: Pour 55-70 parts of EVA resin into a reaction kettle, add the mixed solution in step 1 and 5-12 parts of ferrosoferric oxide composite particles, heat to 45-50° C. and mix well; Step 3: Add 0.3-0.7 parts of antioxidant 1010, 8-12 parts of rosin, and 16-20 parts of paraffin, continue heating to 65-70°C, and mix well; Step 4: adding the uniformly mixed material into a twin-screw extruder for extrusion, and then cooling and granulating to obtain a hot melt adhesive with high viscosity and high shear strength; The twin-screw extruder is divided into three sections: an inlet section, a middle section and an outlet section, and the temperatures thereof are controlled at 75-90°C, 110-125°C and 90-100°C respectively.

2. The process for preparing a hot melt adhesive with high viscosity and high shear strength according to claim 1, characterized in that: The preparation method of the ferroferric oxide composite particles is as follows: S1, pre-treating 10-12g of ferrosoferric oxide; S2, pour the treated ferroferric oxide into 25-30 mL of polyvinyl alcohol aqueous solution, ultrasonically disperse for 25-30 min, and introduce nitrogen for protection; S3, add 5-8g of vinyl acetate dropwise, react for 30-40min, raise the temperature to 75-80°C, add 0.8-1.5mL of initiator, react for 30-35min, then add 5-8g of vinyl acetate dropwise, repeat this operation until all the vinyl acetate is added dropwise; S4, adding 10-12 mL of divinylbenzene to adjust the pH value of the solution to 6.8-7.2; S5. Heat to 80-85°C and keep warm for 55-60 minutes; S6. After natural cooling, place in a magnet. After adsorption is completed, pour out the supernatant and rinse the adsorbate with deionized water 3-5 times; S7. Dry in a vacuum drying oven at 70-75°C for 8-10 hours to obtain ferrosoferric oxide composite particles.

3. The process for preparing a hot melt adhesive with high viscosity and high shear strength according to claim 2, characterized in that: In the S3, the added amount of vinyl acetate is 40-50g.

4. The process for preparing a hot melt adhesive with high viscosity and high shear strength according to claim 2, characterized in that: The mass fraction of the polyvinyl alcohol aqueous solution is 4%; and the initiator is ammonium persulfate.

5. The process for preparing a hot melt adhesive with high viscosity and high shear strength according to claim 2, characterized in that: In S1, the specific method of pretreatment is: pour 320-350 mL of deionized water into 10-12 g of ferroferric oxide, and perform ultrasonic dispersion, heat to 80-85°C, drop 8-11 mL of oleic acid, stir, and react for 50-60 minutes, rinse with deionized water and anhydrous ethanol for 4-6 times, and then place in a vacuum drying oven to dry for 22-24 hours.

6. The process for preparing a hot melt adhesive with high viscosity and high shear strength according to claim 5, characterized in that: The pretreatment process of the ferroferric oxide is carried out in a nitrogen atmosphere; when the oleic acid is added dropwise, the drop rate is 4-6 drops / min; and the stirring rate during the reaction is 300-350 r / min.

7. The process for preparing a hot melt adhesive with high viscosity and high shear strength according to claim 1, characterized in that: The preparation method of the modified nano calcium carbonate is: Ⅰ. Pour hexadecyltrimethylammonium bromide into deionized water at room temperature and stir until completely dissolved to obtain solution 1; Ⅱ. Add nano calcium carbonate to anhydrous ethanol under stirring, stir for 10-15 minutes, and then ultrasonically disperse for 15-20 minutes to obtain solution 2; III. Mix solution 1 and solution 2, and then add ammonia water to adjust the pH value of the solution to 9.6-10; IV. Centrifugal separation, and drying the precipitate in a vacuum drying oven at 85-90°C to obtain modified nano calcium carbonate.

8. The process for preparing a hot melt adhesive with high viscosity and high shear strength according to claim 7, characterized in that: The weight proportions of the components added in the modified nano-calcium carbonate are: 3-7 parts of hexadecyltrimethylammonium bromide, 20-26 parts of deionized water, 35-50 parts of anhydrous ethanol, and 22-28 parts of nano-calcium carbonate.

Citation Information

Patent Citations

  • Preparation method of cold-resistant hot melt adhesive

    CN106010368A

  • Preparation of thiophilic magnetic compound microballoons and method for separating immune globulin G using the compound microballoons

    CN101279246A

  • EVA hot melt adhesive based on CaCO3 filler and modifying method thereof

    CN107254265A

  • Method for improving interfacial compatibility of EVA / Fe3O4 magnetic hot melt adhesive

    CN108192530A

  • PVC composite adhesion film for mold pressing of furniture, and preparation method thereof

    CN109628003A